Exploring Adoption Behaviour and Economic Inspiration Level of Chrysanthemum Growers in Dharmapuri District of Tamil Nadu, India - Jayashree V; Asokhan M (Archives of Current Research International, 2025)
Chrysanthemum cultivation has gained prominence as a profitable floriculture enterprise, particularly in Dharmapuri district, Tamil Nadu, which ranks among the leading chrysanthemum-producing regions in India. This study examines the adoption behaviour of chrysanthemum growers and their level of economic inspiration, highlighting key factors influencing their decisions. A total of 60 farmers were selected using an equal proportionate random sampling method, and data were collected through a well-structured, pre-tested interview schedule. The study employed mean scores to assess the extent of technology adoption and categorized economic inspiration levels based on a five-point continuum scale. The findings revealed that growers had medium level of technology adoption (mean score 2.06), with key practices such as land preparation, propagation, fertilizer application, and pest control showing varying degrees of adherence. Economic inspiration among farmers was found to be a significant driver of adoption, with 40% of growers exhibiting a partial level of economic inspiration, followed by 31.67% at a perfect level and 28.33% at a least level. By addressing these practices, chrysanthemum farming can emerge as a sustainable and profitable enterprise, contributing to the economic upliftment of farmers in the region.